Usefulness of Reticulocyte Hemoglobin Equivalent in Management of Regular Hemodialysis Patients with Iron Deficiency Anemia - Dalimunthe Naomi Niari; Lubis Abdurrahim Rasyid (Sciendo, 2016)
Introduction. Reticulocyte hemoglobin equivalent (RET-He) is a new parameter for evaluating iron status. This study aims to assess diagnostic value and investigate RET-He as early predictor of response to intravenous iron supplementation.